Monitoring and handling of actuator faults in two-tier control systems for nonlinear processes - Liu, Jinfeng; Ohran, Benjamin J.; Muñoz de la Peña, David; Christofides, Panagiotis D.; Davis, James F. (Chemical engineering science, 2010)
This work focuses on the monitoring and reconfiguration of two-tier control systems applied to general nonlinear processes in the presence of control actuator faults. Specifically, a general class of nonlinear process systems is first considered and is controlled by a two-tier control system integrating a local control system using continuous sensing/actuation with a networked control system using asynchronous sensing/actuation. To deal with control actuator faults that may occur in the closed-loop system and eliminate the ability of the two-tier control system to stabilize the process, a fault detection and isolation (FDI) and fault-tolerant control (FTC) system is designed which detects and isolates actuator faults and determines how to reconfigure the two-tier control system to handle the actuator faults and ensure closed-loop stability. The FDI/FTC system uses continuous measurements of process variables like temperature and asynchronous measurements of variables like species concentrations. We develop reconfiguration-based FTC schemes that effectively deal with faults in the actuators of both the local and networked control systems. A detailed mathematical analysis is carried out to determine precise conditions for the stabilizability of the FDI/FTC system. The method is demonstrated using a reactor-separator process consisting of two continuously stirred tank reactors and a flash tank separator with recycle stream.